The Thirty-Nine Steps - Bullard, Nick; Buchan, John; Buchan, John (Oxford :Oxford University Press, 2009)
I turned on the light, but there was nobody there. Then I saw something in the corner that made my blood turn cold. Scudder was lying on his back. There was a long knife through his heart, pinning him to the floor.' Soon Richard Hannay is running for his life across the hills of Scotland. The police are chasing him for a murder he did not do, and another, more dangerous enemy is chasing him as well - the mysterious 'Black Stone'. Who are these people? And why do they want Hannay dead?
BAC
Keywords: Intriga; Espionaje